Correlation between dietary calcium intake and eczema in American adult population - Qianjie Wu; Zitao Guo; Na Zhang; Dake Dong (Scientific Reports)
Abstract Eczema is a common chronic skin condition. Previous studies indicated the dietary factors, such as calcium intake, might influence the onset and progression of eczema in the population of gravidas and infants. However, there was no studies on the correlation between dietary calcium and the adult population. In this study, we aim to investigate the correlation between dietary calcium intake and the prevalence of eczema in adults. The characteristics of adults (≥ 18 years) were collected from the National Health and Nutrition Examination Survey (NHANES) 2005–2006 database. Dietary calcium intake was assessed using the 24-hour dietary recall method. The prevalence of eczema was determined through an allergy questionnaire. Logistic regression modeling was applied to analyze the correlation between dietary calcium intake and eczema prevalence. Restricted cubic spline (RCS) was used to investigate the nonlinear relationship between calcium intake and eczema. A two-stage linear regression model was used to calculate the critical effect of calcium intake on the prevalence of eczema by smoothed curve fitting. Subgroup analyses were performed to explore the effect of different demographic characteristics on the relationship between dietary calcium intake and eczema. Results In this cross-sectional study, we collected 4086 adult samples. There were 1930 males (46.9%) and 2156 females (53.1%), at the average age of 46.7 years, and 266 participants (7.6%) were diagnosed with eczema. Logistic regression results showed there was a significant difference between the third quartile group and eczema compared to the 1st quartile group of dietary calcium (OR: 1.913, 95% CI: 1.024–3.576, P = 0.043). The RCS showed an inverted U-shaped correlation between dietary calcium intake and eczema prevalence (non-linear P-value < 0.05). An increase in calcium intake was associated with an increase in eczema prevalence when the logarithmic value of dietary calcium intake was below 7.089 (OR: 1.790, 95% CI: 1.006–3.183, P = 0.048). These data indicated there was an inverted U-shaped correlation between dietary calcium intake and the prevalence of eczema, which suggested moderate reduction of calcium intake might be beneficial in the incidence of eczema. Further prospective studies are needed to explore causal relationships and optimal calcium intake levels to prevent eczema.